SPTBN2 regulated by miR-214-3p inhibits the proliferation and migration of colorectal cancer cells: SPTBN2 inhibits the colorectal cancer cells - Chen, Chunlin; Zhang, Qianshi; Wang, Bo; Song, Yang; Feng, Zhen; Ren, Shuangyi (Cellular and Molecular Biology, 2023)
Colorectal cancer (CRC) is one of the most common and lethal malignancies. According to our analysis in the GEPIA database, SPTBN2 was found to be significantly elevated in COAD patients.Western blot also verified this result, and SPTBN2 was highly expressed in two types of colorectal cancer cells, Caco2 and HCT-8. Therefore, we knocked down SPTBN2 to investigate its function in colorectal cancer, and the results of CCK-8 and Transwell assays showed that SPTBN2 deletion inhibited the proliferation, migration and invasion of CRC cells. In addition, we found that SPTBN2 may be a target of miR-214-3p through the staebase database. miR-214-3p inhibitors promote CRC cell proliferation, migration and invasion. And inhibition of SPTBN2 partially reversed the effect of miR-214-3p in CRC. Taken together, we demonstrated that SPTBN2 acts as an important target of miR-214-3p in CRC. Our study lays the foundation for the mechanism of CRC.